Discovering Patterns in Textual Data Using SAS Visual Analytic - Majaliwa, Wintuik (Jejaring Penelitian dan Pengabdian Masyarakat, 2023)
Today's generation are more tech savvy than previous generations. They tend to complete their everyday tasks from making their daily schedule to purchasing their daily necessities on the internet. Due to the boom in this culture, e-commerce retail stores have increased their retail sales. According to the United States of America’s Census Bureau, the retail online sales in the year 2012 has peaked at 45.6 billion from the year 2001. This is an increase of 26.9%. This proves that the digital economy is growing and will continue to grow further. In e-commerce platforms there will definitely be a large requirement for logistics which develop a cross organisational support between supply chain management and retail sales. Using text analysis an in depth review of understanding customer satisfaction towards logistical issues to further enhance product delivery and logistical improvements in terms of logistics operations. Mainly using sentiment analysis. Challenges to product delivery are discussed and viable solutions to overcome current or existing logistical issues are presented in this paper.